1992
DOI: 10.1071/ar9921759
|View full text |Cite
|
Sign up to set email alerts
|

Wool fibre tenacity and its relationship to staple strength

Abstract: Wool fibre tenacity and its relationship to staple strength was studied in a pen-feeding trial of 40 New Zealand Romney ewes. A method for estimating fibre tenacity is described based on normalizing fibre breaking load by cross-sectional area measured on fibre fracture-surfaces. The validity of this protocol was demonstrated by showing that (i) fibre diameter measured at the point of rupture was not significantly (P > 0.05) changed by breaking, and (ii) that the tenacity estimate was not significantly (P &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As we have described previously, breaking stress/tenacity and extension of a biological material stretched until failure will correlate with the mechanical properties of its weakest element [31]. For a strip of tissue of uniform material properties, this weakest element will generally correspond to its segment of narrowest cross-sectional dimension with respect to the axis of strain.…”
Section: Methodsmentioning
confidence: 97%
“…As we have described previously, breaking stress/tenacity and extension of a biological material stretched until failure will correlate with the mechanical properties of its weakest element [31]. For a strip of tissue of uniform material properties, this weakest element will generally correspond to its segment of narrowest cross-sectional dimension with respect to the axis of strain.…”
Section: Methodsmentioning
confidence: 97%
“…The almost central POB found in autumn wool may be attributed to the lower FD Av and FD SD recorded during this season (Table 2). In this way, Deng et al (2007) claimed that within staple fiber diameter variations were found to have greater prevalence to breakages, particularly where fiber diameters were at their fineness (Gourdie et al, 1992). Values of ELR increased (P<0.01) in autumn than in spring by about 6%.…”
Section: Wool Productionmentioning
confidence: 95%
“…Total diameter variation has a strong negative phenotypic association with staple strength (Ritchie and Ralph, 1990;Reis, 1992;Schlink et al, 1999). The majority of variations in staple strength were thought to be based on differences in intrinsic fiber strength (Gourdie et al, 1992) and fibers stretching ability (Holman and Malau-Aduli, 2012). According to Schlink et al (1999), staple strength was most highly correlated to within staple variations in fiber diameter.…”
Section: Wool Productionmentioning
confidence: 99%